Analisis Pendapatan dan Kelayakan Usahatani Padi Sawah di Desa Jati - Meri Rosidah; Cecep Pardani (Ma'soem University, 2023)
Based on the results of observations, that the background of this research is about the costs, revenues, income and R/C of Rice Field Farming per Hectare in One Planting Season. This study aims to determine the cost, revenue, income and R/C of Rice Field Farming per Hectare in One Planting Season in Jati Village, Tarogong Kaler District, Garut Regency. The object of this research is the Analysis of Income and Feasibility of Paddy Rice Farming. The type of research used is a survey method, namely observation or investigation by asking for responses from respondents consisting of interviews and questionnaires to obtain good information on a particular problem in a particular area or location. This study takes the case of lowland rice farming on farmers in Jati Village, Tarogong Kaler District, Garut Regency. The results showed that the costs incurred in rice farming per hectare in one planting season were Rp. 33,620,945 and receipts of Rp. 64,443,135.5, so that an income of Rp. 30,822,190.5. The value of R/C rice farming is 1.98, meaning that from every Rp. 1.00 is issued, then the revenue is 1.98 and the income is 0.98.